Research on the mechanism of Bacillus velezensis A-27 in enhancing the resistance of red kidney beans to soybean cyst nematode based on TMT proteomics analysis - Hu, Yi; Ma, Yibing; Wang, Liyi; Luo, Qingqing; Zhao, Zengqi; Wang, Jianming; Xu, Yumei (Frontiers in Plant Science, 2024)
Soybean cyst nematode (SCN) poses a significant challenge to red kidney beans cultivation, resulting in yield losses and quality deterioration. This study investigates the molecular mechanisms using Tandem Mass Tag (TMT) based proteomics technology to explore how the plant growth-promoting rhizobacterium (PGPR) Bacillus velezensis A-27 enhances the resistance of red kidney beans against SCN.The results revealed that out of 1,374 differentially expressed proteins (DEPs) in the red kidney beans roots, 734 DEPs were upregulated and 640 DEPs were downregulated in the A-27 + J2 vs J2 treatment group. KEGG analysis revealed that 14 DEPs were involved in the α-LeA metabolic pathway, crucial for the biosynthesis of jasmonic acid (JA) in plants. Quantitative real-time PCR (qRT-PCR) confirmed the upregulation of 4 key genes (PLA1, AOS, AOC, ACX) in the JA biosynthesis pathway, while enzyme-linked immunosorbent assay (ELISA) demonstrated a significant increase in JA content in the roots. The study demonstrates that B. velezensis A-27 stimulates induced systemic resistance (ISR) in red kidney beans, and induce JA biosynthesis by regulating the expression of key enzymes in the α-LeA metabolic pathway. This enhances the plant's defense against SCN, providing a theoretical foundation for the potential use of B. velezensis A-27 as a biocontrol agent for managing SCN in leguminous crops.